Potensi Penyerapan Karbon Pada Padang Lamun (Seagrass) Di Teluk Youtefa Kota Jayapura, Papua - Linda Hetty Yanne Fatahan; Basa T. Rumahorbo; Korinus Rejauw (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2021)
Climate change has been global warming as greenhouse gas emissions (GHG) caused by increased emissions of gases such as carbon dioxide (CO2), methane (CH4), nitrous oxide (N2O), and chlorofluorocarbons (CFC) so that solar energy is trapped in the earth's atmosphere. Various efforts have been made to reduce the impact of climate change, one of which is by utilizing the oceans and coastal ecosystems as natural CO2 sinks. The purpose of this study was to determine the density, carbon sequestration in biomass and the habitat conditions of seagrass beds conducted in March 2021 in Youtefa Bay, Jayapura Papua. Seagrass density was carried out using the quadrant transect method, carbon content analysis was carried out using the ashing method. The results of the study found 1 species of seagrass, namely Enhalus acoroides, the density values ranged from 85.69 ind/m² - 102.56 ind/m². the value of biomass under the substrate ranged from 3321.75 - 3580.75 gbk/m² which was greater than the value of the biomass above the substrate, which ranged from 720.19 to 955.79 gbk/m², followed by the value of the carbon content under the substrate (roots and rhizomes) ranged from 87.30 – 96.92 g C/m² while the value of carbon content above the substrate (leaf) ranged from 35.99 – 44.84 g C/m². The total carbon stock in Youtefa Bay waters, Jayapura City, Papua ranges from 4859.38 – 6687.89 tons/ha.Key Words: Biomass; Carbon Content; Carbon Sequestration; Ashing Method; Youtefa Bay